Rapid design and implementation of a virtual pain management programme due to COVID-19: a quality improvement initiative. Issue 2 (April 2022) - Williams, Deborah; Booth, Gregory; Cohen, Helen; Gilbert, Anthony; Lucas, Andrew; Mitchell, Chloe; Mittal, Gayatri; Patel, Hasina; Peters, Tamsin; Phillips, Mia; Rudge, Will; Zarnegar, Roxaneh
Background: The COVID-19 pandemic interrupted the delivery of face-to-face pain services including pain management programmes in the United Kingdom with considerable negative impact on patients with chronic musculoskeletal pain. We aimed to develop and implement a remotely delivered pain management programme (PMP) using video-conferencing technology that contains all the core components of a full programme: the 'virtual PMP' (vPMP). By reporting on the process of this development, we endeavour to help address the paucity of literature on the development of remote pain management programmes. Methods: The vPMP was developed by an inter-disciplinary group of professionals as a quality improvement (QI) project. The Model for Improvement Framework was employed with patient involvement at the design phase and at subsequent improvements. Improvement was measured qualitatively with frequent and repeated qualitative data collection leading to programme change. Quantitative patient demographic comparisons were made with a patient cohort who had been on a face-to-face PMP pathway. Results: Sixty-one patients on the PMP waiting list were contacted and 43 met the criteria for the programme. Fourteen patients participated in three vPMP cycles. Patient involvement and comprehensive stakeholder consultation were essential to a robust design for the first vPMP. Continued involvement of patient partners during the QI process led to rapid resolution of implementation problems. The most prominent issues that needed action were technical challenges including training needs, participant access to physical and technological resources, participant fatigue and concerns about adequate communication and peer support. Conclusion: This report demonstrates how a remotely delivered PMP, fully in line with national guidance, was rapidly developed and implemented in a hospital setting for patients with chronic musculoskeletal pain. We also discuss the relevance of our findings to the issues of cost, patient experience, patient preferences and inequities of access in delivering telerehabilitation for chronic pain.